Modeling the consumption of current assets on the basis of the Cauchy problem for forging and pressing production - N. V. Gryzunova; A. A. Khvostova; M. V. Ivanyuk (Вестник Северо-Кавказского федерального университета, 2023)
Lean production is the dominant direction of transformations taking place in industrial enterprises. The benefits of lean manufacturing come from streamlining resource flows, increasing productivity, eliminating waste, and reducing delays. This article discusses the problem of optimizing current assets based on the Cauchy model. The subject of the study is the change in the system of current assets management, taking into account their composition, structure, cyclicality in terms of lean production. The purpose of this article is to consider the constructed model for managing changes in current assets. The methodological basis of this study is an interdisciplinary approach. The findings of the study can be used both to develop the assessment and optimization of current assets at enterprises that switch to lean production and create a "smart factory".